Deregulation, Innovative Entry and Structural Diversity as a Source of Stable and Rapid Economic Growth - Gunnar Eliasson (The Research Institute of Industrial Economics (IUI), 1990)
The importance of free innovative entry (deregulation) for diversity of structure and competition is studied. I demonstrate quantitatively that even with a narrow definition of entry (firms), and given observed entry behavior, successful entrants completely dominate the long run performance characteristics of the economy. Rapid and stable long-run macro-economic growth can only be achieved if innovative competitive entry is vigorous. Free access to markets is a necessary condition, competence a sufficient condition. It is probably wrong to believe that the (ex ante) threat of entry is sufficient for dynamic competition. A growing economy requires a steady showering with optimistic entrants, a few of which tum out ex post to be superior performers. Failing and exiting firms are part of the innovation costs to society for steady and rapid economic growth. The benefits of financial innovations like junk bonds are to reduce barriers to competitive entry to make both successes and failures possible.
Keywords: L25; L50; O40; 330; Economic growth; Deregulation; Structural diversity